THE IMPACT OF NATIONAL CULTURE ON INNOVATION PERFORMANCE OF EUROPEAN COUNTRIES - RYŚ Michał (2017)
Different countries attain different levels of innovation performance, what can be seen in many reports, statistical data, rankings and literature published. Analysis of the previous research suggests that this could be caused by the dissimilarities in their cultures. The goal of this article is to investigate whether a relation between a country's culture and its innovation performance level indeed exists. The research is focused on European Economic Area countries and Switzerland. By applying the models of multiple linear regression to the selected and statistically verińed secondary data taken from reliable sources and further quality assurance of these results, it has been proven that there is an influence of national culture on innovation performance. Characteristics of cultures with a low value of Power Distance and high value of lndulgence might be seen as characteristics demanded by organisations like universities - suggested areas of changes are divided into two main ones, which are positively related with innovation performance: employees (partnership between them and happiness of them) and workplace (flexible working hours as well as optimistic and friendly atmosphere).